What are the most commonly used Modal Particles in German? the analysis of the occurrence of MPs in an authentic corpus based on current discourses - Aquino, Marceli Cherchiglia (The ESPecialist, 2025)
This article aims to investigate the frequency of occurrence of Modal Particles (MPs) in an authorial corpus composed of authentic texts from current genres such as comics, series, music, and social media posts. The corpus is part of teaching material developed for the instruction and learning of MPs in the Brazilian context, utilizing a description of the pragmatic function of these elements based on the minimalist approach (Weydt, 1969; Diewald, 2013; Aquino, 2024a). Although representing a well-defined class of words in the German language, there are still some divergences regarding their classification, especially concerning which elements can be considered MPs and which are more frequent in oral and written communication. Furthermore, the analysis of the occurrence of MPs has stagnated in recent years, which justifies the relevance of studies investigating their occurrence in diverse and contemporary genres. The results of this study represent a significant tool for both a more concrete understanding of the use of MPs and for exploring their didactic possibilities in teaching the German language.